Multi-objective optimization of CO2 recycling operations for CCUS in pre-salt carbonate reservoirs. (September 2022) - Rodrigues, Hydra W.L.; Mackay, Eric J.; Arnold, Daniel P.
Highlights: The optimization methodology can be adapted to coupled CO2 -EOR and carbon storage projects where mineral scale poses a threat to flow assurance. Integrated assessment of the economic, environmental, and operational viability (regarding mineral scale) of CCUS projects in the pre-salt region. Optimized tapered CO2 -WAG designs showed potential to improve reservoir performance and scale management, whilst reducing E&P emissions and total carbon intensity of oil produced. Abstract: This study evaluates the potential of recycling carbon dioxide (CO2 ) in the associated gas in ultra-deepwater pre-salt carbonate reservoirs for Carbon Capture Utilization and Storage (CCUS). We performed compositional subsurface modeling of a hypothetical field for multi-objective optimization, aiming at minimizing carbon emissions whilst maximizing the project's Net Present Value (NPV). Although no absolute reduction in total CO2 emissions was met with economic improvement, all simulated CCUS scenarios yielded a lower carbon footprint oil, with 43.5% reduction in operational emissions and up to 25.5% increase in NPV. The best CCUS case, a tapered Water Alternating Gas (WAG) design, presented break-even oil price of 39.5 USD/STB and operational CO2 abatement cost of negative 94.8 USD/tCO2 abated, also showing significant reduction in number of squeeze treatments and cost of calcite scale management.